Exploring content characteristics and consumer preference factors for webtoon development and recommendation: A focus on never webtoon - Mun, Junhwan (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the influence of shared universe structures and media mix strategies on consumer preferences within the webtoon industry, focusing on Naver Webtoon. The research employs logistic regression analysis and cluster analysis using a dataset of approximately 1,800 webtoons. Variables include media mix status, shared universe affiliation, and other structural features such as age rating and completion status. The results demonstrate that both media mix and shared universe characteristics have a statistically significant positive effect on consumer preferences. Media mix shows the strongest influence, especially in genres like romance and drama, while shared universes enhance engagement, particularly in action and thriller webtoons. These findings suggest that narrative interconnectivity and cross-media expansion are key factors driving webtoon popularity. The study provides actionable insights for webtoon platforms and content creators by highlighting the importance of genre-specific strategies, enhanced recommendation systems, and the strategic use of media mix and shared universes in content planning and platform UX design.